EVALUASI PENERAPAN K3 PADA PEKERJA DI KETINGGIAN DI PT. PLN UIT JBT UPT BEKASI - Nikhen Hanifah Alvianshah (Universitas Widya Gama Mahakam Samarinda, 2023)
Working at altitude is working in a high place that can be risky for orkers to experience injuries if they fall from that place. The Law No. 1 of 1970 states that one of the work activities that need attention from the safety side is work activities carried out at a heightObjectives: The purpose of this study was to evaluate the application of K3 to workers at altitude based on permenaker No. 9 of 2016 on the work of replacing the 500 kV panthograph disconnecting switch (DSP) at PT. PLN UIT JBT UPT Bekasi. This study uses the type of qualitative research that is observaisonal by using a cross sectional approach. Data collection techniques using observation systems and interviews to informants through the text of the interview guidelines. The study was conducted in September 2022. The results showed that the replacement work disconnecting switch panthograph (DSP) is included in the category of types of work at height. The results of observations and interviews show that workers are still less aware of aspects of K3, have not implemented aspects of emergency preparedness, and still use workers who are not yet competent. The work of replacing the disconnecting switch panthograph (DSP) has not implemented the safety requirements for working at height according to Permenaker No. 9 of 2016. This is because there are still some points that have not been met, namely K3 planning, K3 procedures and Labor competence